Primary School Teachers’ Perception About Curriculum 2013 Assessment System - Ika Maryani; Sri Tutur Martaningsih (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
The research is intended to find out: 1)the level of primary school teacher understanding of Curriculum 2013, 2). The level of teacher understanding on the authentic assessment, 3)The difficulties faced by the teacher when doing authentic assessment, and 4)The effort of the teacher to solve those difficulties. In collecting the data, the researcher used questionnaires and interviews to the primary school teachers in Yogyakarta, then analyzed the data using statistic descriptive analysis technique. The results of this research showed that: a) most of the teachers didn’t understand the Curriculum 2013, yet they were not given any training before; b) teachers’ understanding in authentic assessment system were low; c) the teacher were lack of the ability to define the competence, indicators, learning objectives, and also arranging of assessment instrument and final report, d) the teacher effort to solve those difficulties were by joining the training peer discussion, and mentoring by Education Department as well as to the higher education institution.